Pengembangan Sistem B2B E-Commerce berbasis layanan dengan menggunakan MERN Stack (Studi Kasus : Recaka Parfum Surabaya) - Ilham Tubagus Arfian; Tri Astoto Kurniawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Recaka is a perfume manufacturer located in Surabaya that sells products directly to consumers and sells products to be sold and re-marketed through distributors and resellers (members). The business process carried out between Recaka Parfum and its members still has several issues such as frequent errors in sending orders, inefficient payment verification processes, difficulties in monitoring and tracking orders. Recaka also has to anticipate in integrating the system in each of the businesses it owns because Recaka also has businesses in other fields (barbershop and fashion for men), each of which is planned to be developed using a different platform. A service-based B2B E-Commerce system was developed to solve these issues. The system was developed using the waterfall model with an object-oriented approach. A combination of several technologies (stack) consists of MongoDB as a database management system, Express Js as a back-end web framework, React Js as a library for building the user interface, and Node Js as a runtime environment (MERN stack) was used to develop this system. Unit, integration, and validation tests were conducted which resulted in valid values.